Grammatical Number and Donkey Anaphora in English - Gillon, Brendan (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1994)
ABSTRACTThe article extends the analysis of English donkey anaphora, developed by Gareth Evans and improved by Stephen Neale, beyond those cases where the antecedents are singular count noun phrases, to those where the antecedents are either plural count noun phrases or mass noun phrases. The extension is based on an analysis of English grammatical number developed elsewhere cf. Gillon (1992). Its application here requires that a suggestion adopted by Neale—namely, that the grammatical number of pronouns in these cases is semantically inert—be relinquished. It is shown on independent grounds that the suggestion is untenable.